The Social Construction of Gender in the Representation of Dance Communities on Instagram - Ramadhan, Affan Neskisyah; Santoso, Putut Raka; Rachmah, Fitri Annisa; Firdawiya, Firdawiya (Universitas Negeri Makassar, 2025)
This study analyzes the social construction of gender in the visual representations of dance communities on Instagram. Using a descriptive qualitative approach and applying Berger & Luckmann's Social Construction theory and Gender Communication theory, the research examines how dance communities collectively produce and reproduce gender meanings through their content. The results reveal a strong symbolic polarization between femininity and masculinity, externalized through aesthetic choices of costumes, movement composition, and interaction patterns. Femininity is constructed through softness, fragility, and decorative values, while masculinity is represented through strength, stability, and authority. The objectivation process occurs through consistent repetition of representations and digital production techniques (shot angles, filters, editing) that sharpen gender differences. Although limited variations exist, the dominant gender structure is maintained through the sedimentation mechanism of traditional values. The findings show the role of dance communities as agents of gender discourse conservation through digital curatorial practices.